2018
DOI: 10.1186/s12935-018-0583-2
|View full text |Cite
|
Sign up to set email alerts
|

miR-133a function in the pathogenesis of dedifferentiated liposarcoma

Abstract: BackgroundSarcomas are malignant heterogeneous tumors of mesenchymal derivation. Dedifferentiated liposarcoma (DDLPS) is aggressive with recurrence in 80% and metastasis in 20% of patients. We previously found that miR-133a was significantly underexpressed in liposarcoma tissues. As this miRNA has recently been shown to be a tumor suppressor in many cancers, the objective of this study was to characterize the biological and molecular consequences of miR-133a underexpression in DDLPS.MethodsReal-time PCR was us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 41 publications
0
7
0
Order By: Relevance
“…Conversely, the most downregulated miRNAs were miR-6503-5p, miR-196b-3p, miR-196b-5p, miR-133a-3p, and miR-5584-5p. The mature miRNA miR-196b functions as a tumor suppressor during lung carcinogenesis (37), and well-characterized miR-133a has been found to function in a tumor-suppressive manner in as many as five cancers, including breast and colorectal cancer (38).…”
Section: Microrna Profiling Of Cbfa2t3-glis2 Patientsmentioning
confidence: 99%
“…Conversely, the most downregulated miRNAs were miR-6503-5p, miR-196b-3p, miR-196b-5p, miR-133a-3p, and miR-5584-5p. The mature miRNA miR-196b functions as a tumor suppressor during lung carcinogenesis (37), and well-characterized miR-133a has been found to function in a tumor-suppressive manner in as many as five cancers, including breast and colorectal cancer (38).…”
Section: Microrna Profiling Of Cbfa2t3-glis2 Patientsmentioning
confidence: 99%
“…In dedifferentiated liposarcoma (DDLPS), loss of miR-133a could reduce oxidative metabolism, supporting the tumor Warburg effect. Braggio, D. first found that overexpression of miR-133a could increase glycolysis and OXPHOS both in vitro and in vivo ; however, the metabolic change was not sufficient to suppress DDLPS cell proliferation and progression 27 . It was known that glycogen metabolism contributed to cancer development.…”
Section: Mir-133a In Autophagy and Metabolismmentioning
confidence: 99%
“…Similarly, over-expression of miRNA-133a could inhibit the proliferation and regulate mitochondrial function and glycolysis ability of DDL cell lines. However, in vivo experiments showed that exogenous recombinant miRNA-133a had only the ability to regulate cell metabolism, and without proliferation inhibition [61]. Recently, Mazzu et al [62] has found that miR-193b regulates multiple oncogenic signaling pathways (such as PDGFR, TGF, and Wnt) by targeting PDGFR-β, SMAD4 and YAP1 proteins in vitro, and thus miR-193b plays a tumor-suppressing role in the WDL/DDL cell lines.…”
Section: Efficacy Assessment and Prognosis Predictionmentioning
confidence: 99%